Characterization of laser propagation through turbulent media by quantifiers based on the wavelet transform: dynamic study - Zunino, Luciano José (2006)
We analyze, within the wavelet theory framework, the wandering over a screen of the centroid of a laser beam after it has propagated through a time-changing laboratory-generated turbulence. Following a previous work (Fractals 12 (2004) 223) two quantifiers are used, the Hurst parameter, H, and the normalized total wavelet entropy. The temporal evolution of both quantifiers, obtained from the laser spot data stream, is studied and compared. This allows us to extract information on the stochastic process associated with the turbulence dynamics.